2004
DOI: 10.1007/s10562-004-8677-y
|View full text |Cite
|
Sign up to set email alerts
|

Support Effects in Nerol Hydrogenation over Pt/SiO2, Pt/H-Y and Pt/H-MCM-41 Catalysts

Abstract: Chemoselective hydrogenation of nerol was investigated over Pt/SiO 2 , Pt/H-Y and Pt/H-MCM-41 catalysts. The initial total reaction rates decreased in following order:Pt/H-Y > Pt/SiO 2 > Pt/H-MCM-41. Nerol hydrogenation was found to be an apparent structure sensitive reaction. The selectivities to citronellol at 30% conversion of nerol were 65%, 55% and 25% over Pt/SiO 2 , Pt/H-MCM-41 and Pt/H-Y, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Besides hydrogenation, hydrodeoxygenation 11 and decarbonylation also occur. The confirmed hydrodeoxygenation products in nerol hydrogenation are 3,7-dimethyloctene and 3,7-dimethyloctane . Decarbonylation of an unsaturated alcohol could explain the fast catalyst deactivation during nerol hydrogenation at 100 °C .…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…Besides hydrogenation, hydrodeoxygenation 11 and decarbonylation also occur. The confirmed hydrodeoxygenation products in nerol hydrogenation are 3,7-dimethyloctene and 3,7-dimethyloctane . Decarbonylation of an unsaturated alcohol could explain the fast catalyst deactivation during nerol hydrogenation at 100 °C .…”
Section: Introductionmentioning
confidence: 94%
“…The preliminary results in nerol hydrogenation over Rh/Al 2 O 3 catalyst revealed that the selectivity to a desired, intermediate product, citronellol, increased with increasing conversion . Selectivity enhancement in nerol hydrogenation was not, however, observed over a Pt/SiO 2 catalyst . The main aim in this work was to investigate the origin of the selectivity enhancement over Rh/Al 2 O 3 catalyst in nerol hydrogenation by varying the reaction conditions as well as to investigate the catalyst reuse.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations